Development and validation of a reversed-phase high-performance liquid chromatographic method with solid-phase extraction for the quantification of hydrochlorothiazide in ex vivo permeation studies - Onnainty, Renée (2017)
Hydrochlorothiazide (HCT) is a diuretic used to treat hypertension. In order to study its intestinal permeation behavior applying an ex vivo methodology, a rapid, sensitive and selective reversed-phase liquid chromatography (RP-HPLC) method coupled with UV detection (RP-HPLC UV) was developed for the analysis of HCT in TC199 culture medium used as mucosal and serosal solutions in the everted rat intestinal sac model. Also, analytical procedures for the quantification of HCT by RP-HPLC with UV detection required a sample preparation step by solid-phase extraction. The method was validated in the concentration range of 8.05 × 10−7 to 3.22 × 10−5 m for HCT. Chromatographic parameters, namely carry-over, lower limit of quantification (1.4491 × 10−7 m), limit of detection (3.8325 × 10−8 m), selectivity, inter- and intraday precision and extraction recovery, were determined and found to be adequate for the intended purposes. The validated method was successfully used for permeability assays across rat intestinal epithelium applying the ex vivo everted rat gut sac methodology to study the permeation behavior of HCT.